PENGARUH KUALITAS LAYANAN PEMBERIAN KREDIT TERHADAP KEPUASAN NASABAH PADA KOPERASI KARYA ABADI SIMPAN PINJAM SEKAYU - Dadang Syaputra (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determine how big the influence of price, product quality, and location of the buying decision on the food stalls located in the vicinity of Simpang Lima, Semarang. And this research also aims to analyze the most dominant factors that influence on buying decisions of food stalls located in the vicinity of Simpang Lima, Semarang. The population used in this study is consumers who ever or frequently eat on the food stalls located in the vicinity of Simpang Lima, Semarang. The sample in this study are 80 respondents and the techniques used are non-probability sampling technique with the approach of accidental sampling (sampling based on chance). From the analysis result, the indicators in this study are valid and valid variables. And the most dominant factor that influence on purchase decisions are price variables, then the location variable, and the last is the quality of produk variable. The dependent variables in this study are good enough in explaining the independent variable (purchase decisions). Writer’s advice is for food stalls located in the vicinity of Simpang Lima, Semarang need to preserve the good things that have been assessed by consumers and repair the things that not good enough in consumer’s sight.